Intensive care medicine: a multidisciplinary approach! - Aken, Hugo Van (2016)
Intensive care medicine (ICM) is unique in that it deals with the most severely ill patients in almost all fields of medicine. It is demanding in all aspects from a theoretical, practical, co-operational and personal perspective. It is also characterised by a rapid development in diagnostic and treatment options. Furthermore, the organisational and manpower characteristics of European healthcare have been changing over time. Hence, the official status of ICM warrants unbiased consideration.